Assessing global perceptions of India: Policy implications drawn from foreign tourism narratives - Kaurav, Rahul Pratap Singh; Kainthola, Snigdha; Baber, Ruturaj; Tiwari, Pinaz (Turyzm/Tourism, 2024)
This study scrutinizes India’s growing appeal as a tourist destination, accentuated by government initiatives and innovative tourism policies like the e-visa program, Incredible India Campaign 2.0 and digital advancements in the travel sector. With the diminishing impact of COVID-19, there is a noticeable surge in various forms of tourism – inbound, outbound and domestic. The primary focus is to understand the driving factors behind the choice of India as a destination for inbound tourists. This research delves into these motivations, providing a global perspective on India’s attractiveness. A mixed-method approach was employed, utilizing convenience sampling for data collection. The quantitative analysis was based on a survey, informed by a literature review, comprising 390 respondents from 10 diverse Indian destinations. Additionally, 25 qualitative interviews were conducted, aiming to enrich and triangulate the quantitative findings. Exploratory factor analysis (EFA) revealed five predominant motivations among inbound tourists: culinary interests, spiritual pursuits, budget-consciousness, cultural curiosity and natural allure. These findings were substantiated through thematic analysis. The outcomes have significant practical ramifications for destination managers and tourism policy developers in India. By understanding these key motivators, they can devise targeted strategies for enhancing the appeal of India to these specific tourist segments. This study not only aids in refining tourism promotion efforts but also contributes to the academic discourse on tourist motivation offering a fresh international perspective on India’s image as a tourist destination.